PENGARUH PENGGUNAAN HIJAB TERHADAP RELIGIUSITAS PESERTA DIDIK SMA MUHAMMADIYAH 1 PONOROGO - Selvie Astria Augustine; Ahmad Muslich; Nurul Abidin (TARBAWI:Journal on Islamic Education, 2019)
This study was aimed at finding out how the wearing ofhijab on female students in Muhammadiyah 1 Senior High School of Ponorogo, knowing how was the female students’ religiosity in Muhammadiyah 1 Senior High School of Ponorogo and then investigating how big was the influence of wearing a hijab toward the female students’ religiosity in Muhammadiyah 1 Senior High School of Ponorogo. The method of this study utilized ex post facto with a quantitative approach characterizing the causal relationship between the independent and the dependent variable. The subjects of this study were the 9th and 10th grade students of Muhammadiyah 1 Senior High School of Ponorogo with totally 150 students. The instrument trial was conducted in Muhammadiyah 1 Senior High School of Ponorogo involving 70 female respondents of 9th and 10th grade students. The methods of data collection used in this study were observation, questionnaire and documentation. The validity test of the instrument was using the Moment Product correlation while the raliability test was appliying the Alpha Crobach formula. Whereas, the analysis of this study was utilizing simple linear regression intending to manage the data obtained from the results of distributing questionnaires to female students of 9th and 10th grade students.The results of the research obtained by researcher in using simple linear regression analysis, disclosed a significant effect between the wearing of hijab and the female students’ religiosity in Muhammadiyah 1 Senior High School of Ponorogo where its significance value of 0,000 0,05, so it can be concluded that the variable X or hijab, affected the variable Y or religiosity, because the value of t(count) t(table).